A new Andean species of Philodryas (Dipsadidae, Xenodontinae) from Ecuador - Zaher, Hussam; Arredondo, Juan C.; Valencia, Jorge H.; Arbeláez, Ernesto; Rodrigues, Miguel T.; Altamirano-Benavides, Marco (Zootaxa, 2014)
We describe a new species of Philodryas from the highlands of southern Ecuador. The new species is distinguished from all known species of Philodryas by a unique combination of coloration, scalation, and hemipenial characters. The new species resembles Philodryas simonsii in color pattern. However, they differ notoriously by their hemipenial morphology. The three other trans-Andean members of the genus (Philodryas simonsii, Philodryas chamissonis, and Philodryas tachymenoides), along with the new species, compose a probably monophyletic group that may be characterized by the presence of ungrooved postdiastemal teeth in the maxilla. Unlike most species of the genus Philodryas, the new species shows a restricted distribution, being apparently endemic to a small region of high-altitude (3150–4450m) grasslands in the southern Andes of Ecuador.